Study on Avi-fauna Diversity in Mangrove Area in Aceh Besar Post Tsunami 2004 - Ruskhanidar R; Muhammad Hambal (Jurnal Kedokteran Hewan, 2007)
The research was conducted after tsunami destroyed mangrove in Aceh Besar coastal area, whichserves as waterfowl habitat. This study was aimed to find out bird diversity and abundant after tsunamidisaster. The study was conducted in Kecamatan Mesjid Raya, Aceh Besar, focusing on bird biodiversityand its number based on habitat type, using count dot survey technique. The study revealed that as manyas eight waterfowl species from four families were found. The variety of bird species in the researchlocation was low, ie; 1.2196 for fish pond, 1.7257 for muddy land, and 1.2528 for vegetation area. The lowlevel of biodiversity indicated fragmented habitat in the mangrove area.Keywords: mangrove conservation, bird biodiversity index, bird conservation